Studi Masa Bait Suci Kedua: Analisis terhadap Gulungan Perang (1QM, 1Q33, 4Q491–7, 4Q471) - Andrew Lucas Tjong; Jonathan Octavianus (Sekolah Tinggi Teologi Bethel Ambon, 2024)
The discovery of the Dead Sea Scrolls in the mid-20th century opened up a significant treasure trove for the study of Second Temple Judaism. One of the most striking texts is the War Scroll (1QM) and its associated fragments (1Q33, 4Q491–497, 4Q471), which presents an eschatological narrative of divine warfare between the Sons of Light and the Sons of Darkness. This study aims to comprehensively examine the War Scrolls to understand their content, structure, theological meaning, and historical significance within the Dead Sea Scrolls and their relationship to the biblical text. This qualitative, literature-based study applies a historical-philological approach to analyze the manuscript’s paleography (Herodian Book-Hand), content analysis to dissect the text’s structure, and comparative analysis to compare the theology of the scrolls. The analysis shows that the War Scrolls are complex, multi-genre documents that combine military regulations, tactical strategies, and liturgical rhetoric. Paleographically, this manuscript belongs to the Herodian Book-Hand of the 1st century BC to the 1st century AD. This text represents an ideological synthesis of the Community Rules and the Damascus Document, reflecting the life principles of the Qumran community into a strategy for physical and spiritual warfare in the end times. Furthermore, this text adapts the Old Testament tradition of holy war (such as the prophecies of Daniel and Ezekiel) and shares apocalyptic patterns with the New Testament (Book of Revelation and Pauline Epistles) although it differs in its messianic exclusivity. The War Scroll represents the dramatic culmination of the theological system of the Qumran community, depicting their active role as instruments of future divine judgment. This study contributes significantly to providing a historical framework for the development of Second Temple Period biblical theology.